Traversable Lorentzian wormholes in higher dimensional theories of gravity. (October 2019) - Baruah, Anshuman; Deshamukhya, Atri
Abstract: Wormhole solutions in classical general relativity are unstable and hence non traversable. Morris and Thorne discovered a traversable wormhole solution that required the energy momentum tensor of matter sources to violate various energy conditions and are out of the purview of the standard model of particle physics. The search for traversable wormhole solutions in modified theories of gravity has been of significant interest in the decades after Morris and Thorne first published their results as such violations may be avoided in such theories. This work comprehensively reviews traversable wormhole solutions in higher dimensional extensions of general relativity that satisfy the various energy conditions with an in depth look at the matter sources and the various constraints on the parameters of the theories to make the energy momentum of the matter sources respect the energy conditions.